Skin injuries in hospitalized elderly - Grden, Clóris Regina Blanski; Ivastcheschen, Taís; Cabral, Luciane Patrícia Andreani; Reche, Péricles Martim; Oliveira, Daniele Alaide de Siqueira de; Bordin, Danielle (Estima – Brazilian Journal of Enterostomal Therapy, 2019)
Objective: To identify the prevalence of skin injuries in hospitalized elderly. Method: Cross-sectional study with 202 elderly patients selected for convenience and hospitalized in a hospital in Parana (Brazil). Data were collected between September 2017 and January 2018. The Mini-mental State Examination and the physical examination of nursing in the elderly were used. Data were submitted to the exploratory analysis and described by absolute frequency, percentage, means and standard deviations. Results: Women predominance (51%), age range between 60-69 years (42.5%), married (52%) and low educational level (59.4%). It was identified that 128 (63.4%) elderly had clean scalp; 116(57.4%), skin with normal coloring; 104 (51.5%), normal turgor; 138 (68.3%), normal temperature; 160 (79.2%) of fi ne thickness; 101 (50%), soft texture; 144 (71.3%) with scar; 182 (90.1%), sensitivity; and 152 (75.3%), pruritus. Prevalence of eutrophic body mass index (38.6%) and 176 (87.1%) elderly had skin injuries; 152 (75.3%) had primary injuries and 151 (74.7%), secondary injuries. Conclusion: The study identified the high index of skin injuries in hospitalized elderly. The results are expected to make nurses aware of the importance of the physical examination of the skin as a fundamental step in planning preventive, monitoring and care actions.